NH3-Induced In Situ Etching Strategy Derived 3D-Interconnected Porous MXene/Carbon Dots Films for High Performance Flexible Supercapacitors - Wang, Yongbin; Chen, Ningjun; Zhou, Bin; Zhou, Xuefeng; Pu, Ben; Bai, Jia; Tang, Qi; Liu, Yan; Yang, Weiqing (Nano-Micro Letters, 2023)
2D MXene (Ti3CNTx) has been considered as the most promising electrode material for flexible supercapacitors owing to its metallic conductivity, ultra-high capacitance, and excellent flexibility. However, it suffers from a severe restacking problem during the electrode fabrication process, limiting the ion transport kinetics and the accessibility of ions in the electrodes, especially in the direction normal to the electrode surface. Herein, we report a NH3-induced in situ etching strategy to fabricate 3D-interconnected porous MXene/carbon dots (p-MC) films for high-performance flexible supercapacitor. The pre-intercalated carbon dots (CDs) first prevent the restacking of MXene to expose more inner electrochemical active sites. The partially decomposed CDs generate NH3 for in situ etching of MXene nanosheets toward 3D-interconnected p-MC films. Benefiting from the structural merits and the 3D-interconnected ionic transmission channels, p-MC film electrodes achieve excellent gravimetric capacitance (688.9 F g−1 at 2 A g−1) and superior rate capability. Moreover, the optimized p-MC electrode is assembled into an asymmetric solid-state flexible supercapacitor with high energy density and superior cycling stability, demonstrating the great promise of p-MC electrode for practical applications. Highlights: 1 Porous MXene (p-MC) films with 3D-interconnected ion transmission paths are constructed by NH3-induced in situ etching strategy. 2 The flexible p-MC film electrodes exhibit a superior capacitance of 688.9 F g−1 with a good rate capability. 3 The as-assembled p-MC solid-state flexible supercapacitors reveal superior electrochemical performance (99.7 F g−1 at 1 A g−1) and excellent flexibility.